RESULTS OF THE PHYSICAL EDUCATION TEACHER FROM THE SELF-ASSESSMENT SYSTEM - Shaalimov Mukhtorsho Adkhamovich (American Journals Publishing, 2023)
The article suggests that the Theory of Self-Determination of Physical Education (SPT-PE) methodology offers a useful platform for studying the psychological needs of physical education teachers and their personal, professional and environmental characteristics. The results showed that the self-assessment questionnaire is a valid and accurate tool for evaluating teacher performance. In addition, this tool can undoubtedly improve the knowledge, understanding, motivation and attitude of the teacher towards teaching.
Keywords: physical education, teachers, motivation, self-determination.